Cardiovascular effects of tumour necrosis factor α antagonism in patients with acute myocardial infarction: a first in human study. Issue 18 (10th April 2013) - Padfield, Gareth J; Din, Jehangir N; Koushiappi, Elena; Mills, Nicholas L; Robinson, Simon D; Cruden, Nicholas Le May; Lucking, Andrew John; Chia, Stanley; Harding, Scott A; Newby, David E
Abstract : Objective: The inflammatory cytokine, tumour necrosis factor α (TNF-α), exerts deleterious cardiovascular effects. We wished to determine the effects of TNF-α antagonism on endothelial function and platelet activation in patients with acute myocardial infarction. Design and setting and patients: A double-blind, parallel group, randomised controlled trial performed in a tertiary referral cardiac centre. 26 patients presenting with acute myocardial infarction randomised to receive an intravenous infusion of etanercept (10 mg) or saline placebo. Main outcome measures: Leucocyte count, plasma cytokine concentrations, flow cytometric measures of platelet activation and peripheral vasomotor and fibrinolytic function were determined before and 24 h after study intervention. Results: Consistent with effective conjugation of circulating TNF-α, plasma TNF-α concentrations increased in all patients following etanercept (254±15 vs 0.12±0.02 pg/ml; p<0.0001), but not saline infusion. Etanercept treatment reduced neutrophil (7.4±0.6 vs 8.8±0.6×10 9 cells/l; p=0.03) and plasma interleukin-6 concentrations (5.8±2.0 vs 10.6±4.0 pg/ml; p=0.012) at 24 h but increased platelet–monocyte aggregation (30±5 vs 20±3%; p=0.02). Vasodilatation in response to substance P, acetylcholine and sodium nitroprusside, and acute tissue plasminogen activator release were unaffected by either treatment (p>0.1 for all). Conclusions: Following acute myocardial infarction, etanercept reduces systemic inflammation but increases platelet activation without affecting peripheral vasomotor or fibrinolytic function. We conclude that TNF-α antagonism is unlikely to be a beneficial therapeutic strategy in patients with acute myocardial infarction.